STATUS OF THE COTTON LEAF CURL VIRUS DISEASE SEVERITY IN THE BATHINDA DISTRICT OF PUNJAB (Journal of Plant Disease Sciences, 2017)
ABSTRACT The studies were done to record the cotton leaf curl virus disease (CLCuD) severity through Percent Disease Index (PDI) of cotton at the farmer's field in the Bathinda districts of the South Western Region of Punjab during Kharif season in the year 2015 and 2016. PDI of the CLCuD recorded (25.33 to 72.67%) in the 20 villages surveyed in the year 2015 and (0.00 to 34.33%) in the 42 villages surveyed in the year 2016, respectively. The maximum PDI 72.67% recorded in US Agriseeds US 21BG II (Un-recommended) in Village Jodhpur and 34.33% in SRCH 666 BG II (Un-recommended) in village Bhucho Kalan of the Bathinda district in the year 2015 and 2016,respectively. PDI of the cotton leaf curl virus disease was found to be at the higher range in the year 2015 as compared to 2016. The deviations in the PDI were observed in both the years because of the varied agro-climatological situations, varieties/hybrids grown, awareness among the farmers regarding fertilizer application, application of pesticides, eradication of weeds/host plants acting as alternate or collateral host of the vector whitefly, cultural practices etc.
Keywords: Cotton leaf curl virus disease (CLCuD), severity, Bt Cotton, Hybrids.